Numerical simulation for magnetic dipole in Darcy–Forchheimer flow of diamond $$-{\varvec{S}}{\varvec{i}}{\varvec{C}}-Co_{3}{O}_{4}/$$ - S i C - C o 3 O 4 / diathermic oil based trihybrid nanofluid with porous medium and arrhenius activation energy - Munawar Abbas; Dyana Aziz Bayz; Nizomiddin Juraev; Humaira Kanwal; Ansar Abbas; Jihad Younis; Ibrahim Mahariq (Discover Applied Sciences)
Abstract This proposed model aims to analyze the characteristics of heat generation and activation energy on the Darcy-Forchheimer flow of Diamond $$-SiC-{\text{Co}}_{3}{\text{O}}_{4}/$$ - S i C - Co 3 O 4 / diathermic oil base trihybrid nanofluid under velocity slip conditions, porous medium and magnetic dipole moment. The trihybrid nanoliquid (Diamond $$-SiC-{\text{Co}}_{3}{\text{O}}_{4}/DO$$ - S i C - Co 3 O 4 / D O ) flow model consists of nanoparticles of Cobalt oxide ( $${\text{Co}}_{3}{\text{O}}_{4})$$ Co 3 O 4 ) , diamond $$(ND),$$ ( N D ) , and silicon carbide $$(SiC)$$ ( S i C ) dissolved in diathermic oil (DO). The magnetic dipole has an impact on the subject flow, which is examined on a stretched surface. Taking into consideration the movement of the slip conditions and magnetic dipole increases the fluid model’s uniqueness. By using this approach, the thermal management systems’ heat transfer efficiency can be increased, such as those used to cool electronic equipment and reactors where accurate temperature control is essential. It’s also useful for designing cutting fluids and sophisticated lubricants, where higher viscosity and thermal conductivity are necessary for best results. The simulation can also be used to create new heat exchangers and solar collectors based on nanofluids, which will increase the efficiency of energy conversion. The knowledge gathered from these simulations has the potential to improve chemical processing, especially when it comes to maximizing reactions and the synthesis of materials in regulated magnetic and thermal conditions. By applying the proper similarity transformations, the MATLAB solver bvp4c package finds the mathematical solution to the system of ODEs (ordinary differential equations) that are formed from the leading PDEs (partial differential equations). It is revealed that in terms of heat transmission capacities, the trihybrid nanofluid works noticeably better than the hybrid nanofluid and nanofluid. As hydrodynamic interactions and slip parameters increase, the velocity decreases. Graphical Abstract